Training professional skills using the Latin language (the case of medical specialties) - Elvira Vitalievna Bibikova (Вестник Майкопского государственного технологического университета)
The relevance of the research is due to the fact that the study of the Latin language in a medical university has a purely professional orientation. The main goal of mastering this discipline is to train competent specialists to be proficient in professional terminology. Within the framework of this research, an attempt has been made to demonstrate the possibilities of the Latin language in teaching professional skills of future doctors and pharmacists. The article discusses three subsystems of medical terminology: anatomical-histological, clinical and pharmaceutical ones. As for the anatomical and histological section, typical mistakes and difficulties faced by students have been analyzed, and examples of tasks used by the author to solve these problems given. In the clinical section, the emphasis is made on the tasks that allow you to create an atmosphere of professional activity in the classroom and bring it closer to practical activity. The development of the pharmaceutical section is aimed at forming the terminological competence of future medical workers in the field of pharmaceutical terminology and general formulation. The author gives a brief overview of the material studied at this stage, and gives examples of practical tasks for its better assimilation. All the materials and exercises described in the article are used by the author in the process of teaching Latin in a medical university. Empirical methods, methods of comparison and analysis have been used in the research.As a result, it has been shown that successful teaching professional skills at a medical university is largely possible due to the study of the Latin language.